Respostas
respondido por:
1
(-5)+(-3).(-4)-(-10).(-2)=
-5 + ( +12 ) - ( + 20 ) =
-5 + 12 - 20 =
+12 - 5 - 20 =
+ 12 - 25 =
- 13
-5 + ( +12 ) - ( + 20 ) =
-5 + 12 - 20 =
+12 - 5 - 20 =
+ 12 - 25 =
- 13
respondido por:
0
*sinais diferentes/-
*sinais iguais/+
*e se resolve primeiro as multiplicações e divisões então
(-5)+(+12)-(+20)
-5+12-20=-13
*sinais iguais/+
*e se resolve primeiro as multiplicações e divisões então
(-5)+(+12)-(+20)
-5+12-20=-13
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás